Factors influencing mothers' decision to breastfeed in Hospital Universiti Sains Malaysia (Hospital USM) - Ridzuan, Nurul Syimir Md (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2013)
The purpose of this descriptive study was to identify the factors influencing mothers’ decision to breastfeed in Hospital Universiti Sains Malaysia (Hospital USM). Mother’s knowledge regarding breastfeeding and several factors including personal, social, cultural, facilities and environmental was identified through this study. A convenience sample of 101 primigravida and multigravida mother who admitted into Hospital USM was recruited. The mothers were selected using stratified, random sampling technique. Data were obtained using self-administered questionnaire, adapted questionnaires from Alina & Zaharah (2010) and Kong & Lee (2004) to determine the mother’s knowledge regarding breastfeed and to identify the factors influencing mother’s decision to breastfeed. The data were analyzed with SPSS version 20 using descriptive statistic, Chi-square test for answering the research questions. Result showed that there was significant association between level of mothers’ knowledge and mothers’ decision to breastfeed (/?=0.012). Besides, result also showed that there is a significant association between factors influencing mothers’ decision to breastfeed and mothers’ decision to breastfeed. All the factors involved that are personal (p=<0.001), social (p=0.002), cultural (p=<0.001), facilities and environmental (p=<0.001). In conclusion, the findings of this study provide information for nurses and administrative department regarding factors that influencing mothers’ decision to breastfeed in Hospital USM.